2017
DOI: 10.1051/sbuild/2017001
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state CFD modelling and experimental analysis of the local microclimate in Dubai (UAE)

Abstract: Abstract. Rapid urban growth and development over the past few years in Dubai has increased the rate at which the mean maximum temperatures are rising. Progressive soaring temperatures have greater effect of heat islands that add on to the high cooling demands. This work numerically explicated the effect of HIs in a tropical desert climate by adopting Heriot-Watt University Dubai Campus (HWUDC) as a case study. The study analysed thermal flow behaviour around the campus by using Computational Fluid Dynamics (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Fatima et al (2017) simulated the temperature and wind field with a CFD approach and performed a comparative analysis based on a field measurement dataset. The average temperature deviation was 11%, and the average wind speed deviation was 19% [ 46 ]. These results indicated that the distribution of and changes in the urban space thermal and wind environment were predicted with high accuracy based on the CFD model.…”
Section: Cfd-based Simulation Methods For the Ustementioning
confidence: 99%
See 1 more Smart Citation
“…Fatima et al (2017) simulated the temperature and wind field with a CFD approach and performed a comparative analysis based on a field measurement dataset. The average temperature deviation was 11%, and the average wind speed deviation was 19% [ 46 ]. These results indicated that the distribution of and changes in the urban space thermal and wind environment were predicted with high accuracy based on the CFD model.…”
Section: Cfd-based Simulation Methods For the Ustementioning
confidence: 99%
“…Dimoudi et al (2014) changed the roads and streets in a model from cement mixed with clay to cold materials, used CFD to simulate the temperature field distribution, and found that the surface temperature dropped by 6.5 °C [ 92 ]. According to the results of CFD simulations of wind and heat environments, Fatima et al (2017) found that hot spots in high-temperature areas in cities have a certain correlation with low wind speeds [ 46 ]. Undeveloped areas, such as natural soil, grassland, woodland, and cultivated land areas that have been artificially developed, are characterized by good water permeability and can convert absorbed solar radiation energy into latent heat energy, which can effectively mitigate the rate of increase in surface temperature.…”
Section: Quantitative Simulations Of the Uste Based On Cfd Considering The Underlying Surface Dynamicsmentioning
confidence: 99%
“…Considering the simplifications assumed by the VOF method, which are related to its computational efficiency, the 20% error for the liquid holdup and 12% for the pressure drop was considered acceptable. This was also based on the fact that in CFD studies, especially of multiphase flow or gas modeling, an error of up to 20% or even 30% is not unusual (Guerrero et al, 2017;Fatima and Chaudhry, 2017;Rivas et al, 2019).…”
Section: Experimental Comparisonmentioning
confidence: 99%
“…The interactions between the urban environment and the stadium structures as well as the wind comfort conditions on pedestrian level have also attracted great interest [10][11][12]. Finally, thermal comfort studies, employing dynamic thermal modelling and CFD techniques, were also conducted to assess thermal discomfort and temperature distribution on stadia [2,[13][14][15]41] and energy consumption requirements [16,17,42].…”
Section: Previous Related Workmentioning
confidence: 99%
“…The algorithm performs an elitist non-dominated sorting according to the set objectives. The theoretical background can be found in [39,41].…”
Section: Output Parametermentioning
confidence: 99%